Effective expression of Drebrin in hippocampus improves cognitive function and alleviates lesions of Alzheimer's disease in APP (swe)/PS1 (ΔE9) mice - Liu, Yan (CNS Neurosci Ther, 2017)
AIMS: Alzheimer's disease (AD), a progressive development dementia, is increasingly impacting patients’ living conditions worldwide. Despite medical care and funding support, there are still no highly individualized drugs and practical strategies for clinical prevention and treatment. Developmentally regulated brain protein (abbreviated as Drebrin or Dbn, also known as Dbn1 in mouse) exists in neurons, especially in dendrites, and is an actin‐binding protein that modulates synaptic morphology and long‐term memory. However, the majority of previous studies have focused on its upstream proteins and neglected the impact Drebrin has on behavior and AD in vivo. METHODS: Here, we tracked the behavioral performances of 4‐, 8‐, 12‐, and 16‐month‐old AD mice and investigated the expression level of Drebrin in their hippocampi. A Pearson correlation analysis between Drebrin levels and behavioral data was performed. Subsequently, 2‐month‐old AD mice were injected with rAAV‐zsGreen‐Dbn1 vector, composing the APP/PS1‐Dbn1 group, and sex‐ and age‐matched AD mice were injected with rAAV‐tdTomato vector to serve as the control group. All mice were conducted behavioral tests and molecular detection 6 months later. RESULTS: (i) The expression of Drebrin is decreased in the hippocampus of aged AD mice compared with that of age‐matched WT and young adult AD mice; (ii) cognitive ability of APP/PS1 mice decreases with age; (iii) Drebrin protein expression in the hippocampus correlates with behavioral performance in different aged AD mice; (iv) cognitive ability improved significantly in APP/PS1‐Dbn1 mice; (v) the expression level of Drebrin in APP/PS1‐Dbn1 mouse hippocampus was significantly increased; (vi) the pathological lesion of AD was alleviated in APP/PS1‐Dbn1 mice; (vii) the filamentous actin (F‐actin) and microtubule‐associated protein 2(MAP‐2) in APP/PS1‐Dbn1 mice were notably more than control mice. CONCLUSION: In this study, an effective expression of Drebrin improves cognitive abilities and alleviates lesions in an AD mouse model. These results may provide some valid resources for therapy and research of AD.